Clinical Features and Prognostic Factors of Acute Ischemic Stroke Related to Malignant Gastrointestinal Tumor - Liu, Yating; Li, Xin; Song, Feixue; Yan, Xin; Han, Zhijian; Tang, Futian; Li, Yumin (Frontiers in Neurology, 2021)
Objectives: To analyze the clinical and imaging features of acute ischemic stroke (AIS) related to gastrointestinal malignant tumor, and to explore the prognostic factors. Methods: Clinical data of consecutive patients with gastrointestinal malignant tumor complicated with AIS admitted to the Department of Neurology and Oncology in Lanzhou University Second Hospital from April 2015 to April 2019 were retrospectively analyzed. Patients were divided into good prognosis (mRS 0–2) and poor prognosis (mRS > 2) based on a 90-day mRS score after discharge. The multivariate logistic regression model was used to analyze the prognostic factors. Results: A total of 68 patients were enrolled with an average age of 61.78 ± 6.65 years, including 49 men (72.06%). There were 18 patients in the good prognosis group and 50 patients in the poor prognosis group. The univariate analysis showed that Hcy, D-dimer, thrombin–antithrombin complex (TAT), and three territory sign in magnetic resonance imaging (MRI) were the risk factors for poor prognosis. Multivariate analysis showed that increased D-dimer (OR 4.497, 95% CI 1.014–19.938) and TAT levels (OR 4.294, 95% CI 1.654–11.149) were independent risk factors for the prognosis in such patients. Conclusion: Image of patients with gastrointestinal malignant tumor-related AIS is characterized by three territory sign (multiple lesions in different vascular supply areas). Increased TAT and D-dimer levels are independent prognostic risk factors. TAT is more sensitive to predict prognosis than D-dimer.